Enhancing Network Security Skills using a Problem-Based Learning Approach in Cisco Packet Tracer Simulation Practices - Azizah, Suti Mega Nur; Suswanto, Hary; Ramadhani, Syaifudin (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
The lack of understanding among students with kinesthetic learning styles regarding computer network concepts, particularly in digital security skills, requires a more practical and contextual learning approach. This study evaluates the efficacy of the Problem-Based Learning (PBL) approach, supported by Cisco Packet Tracer simulation, in enhancing student competencies in informatics subjects. This study used a pre-experimental design with a one-group pretest-posttest design approach. One experimental class was given learning using simulation-based PBL, and measurements were taken before and after treatment. The findings indicated that the implementation of PBL via Cisco Packet Tracer simulation markedly enhanced students' network security competencies and fostered critical thinking and problem-solving abilities. This study demonstrates that integrating PBL and digital simulation can be an effective strategy in informatics education. Recommendations for future research include the use of more robust experimental designs with comparison groups, as well as the exploration of immersive learning technologies such as augmented reality (AR) to create more interactive and industry-relevant learning experiences.